Exports, Exchange Rates and Productivity: An Analysis of the Japanese Manufacturing Sectors - Kato, Atsuyuki (European Journal of Economics and Business Studies, 2016)
This paper examines the effects of exchange rate changes and productivity on manufacturing exports. Using the dataset of the Japanese manufacturing firms during the period, 2002 – 2012, we discuss if exchange rate fluctuations deter export activities and if productivity and markup differences affect it. For this study, we estimate both firm specific productivity and markups by the production function based approaches and incorporate them into the Heckman sample selection model. Our results show exchange rates are important factors to affect firm-level exports as a whole while temporal aggregation should be carefully considered. In addition, this study also reveals that productivity and markup give different impacts on firm-level exports across industries. In the transportation equipment industry, negative effects of appreciation on exports are partly mitigated by higher productivity. Markups are positively related to exports in the electronics industry while negative in the transportation equipment. Neither productivity nor markup absorbs the impact of exchange rate changes in the machinery industry. Those findings imply that stability of exchange rates is very important while the effective trade policy may vary across industries following their trade structure.